Project management in boundary spanned teams - diversified directions of social exchange. The meta-analytical approach = Zarządzanie projektami w zespołach o rozszerzonych granicach a problem wymiany społecznej - podejście metaanalityczne - Mazur, Karolina (Zielona Góra: Faculty of Economics and Management Press)
The conceptual model of the types of social exchange in project teams has been presented in the study. The perspective of a boundary spanned organization has been accepted as the basis of the analysis. The author conducted a critical review of literature in the area of relation between the quality of social exchange (referred to models: LMX, TMX and MMX) and such variables as: IP, OCB, OCBO, OCBI and COCB. The analysis included 87 research studies. A vertical and horizontal meta-analysis was made. The legitimacy of a conceptual model has been confirmed. The results of analysis indicated future research directions for independent research projects.
Keywords: zarządzanie projektami; zespoły projektowe; rozszerzanie granic; wydajność indywidualna; metaanaliza; project management; boundary spanning; individual performance; meta-analytical